EXPLICIT EXPRESSION AND DERIVATION VIA DIRECT PROOF
The explicit expression for $\phi$ you are asking for is the following:
Lemma:
Given the Gaussian RBF Kernel $K_\sigma$ between two $n$-dimensional vectors ($x$ and another), for each $j$ from 0 to infinity and for every combination of $n$ indices (labeled as $k$) that add up to $j$, the feature vector $\phi(x)$ has a feature that looks like this:
$$
\phi_{\sigma, j, k}(x) = c_{\sigma, j}(x) \cdot f_{j, k}(x)
$$
Where:
$$
\begin{aligned}
c_{\sigma, j}(x) &= \frac{K_\sigma(x, 0)}{\sigma^j \sqrt{j!}}\\
f_{j, k}(x) &= \begin{pmatrix} j\\k_1,k_2, \dots, k_n \end{pmatrix}^{\frac{1}{2}} \prod_{d=1}^n{x_d^{k_d}}
\end{aligned}
$$
This can be directly derived as follows:
Definitions:
$$
\begin{aligned}
K_\sigma(x, y) = &e^{-\frac{\|x-y\|_2^2}{2\sigma^2}}\\
\epsilon := &e^{\frac{1}{\sigma^2}}\\
\epsilon^x = &\sum_{j=0}^{\infty}\left\{ \frac{x^j}{\sigma^{2j} \cdot j!} \right\}\\
(x_1 + x_2 + \dots + x_n)^j = &\sum_{k_1+k_2+\dots+k_n=j}\left\{ \begin{pmatrix} j\\k_1,k_2, \dots, k_n \end{pmatrix} \prod_{d=1}^n{x_d^{k_d}} \right\}\\
\end{aligned}
$$
Direct Proof:
First, we decompose the squared euclidean distance into its components, and perform the Taylor expansion for the $xy$ component:
$$
\begin{aligned}
K(x,y)= &e^{-\frac{\|x-y\|_2^2}{2\sigma^2}} =\epsilon^{\langle x, y \rangle} \cdot\epsilon^{-\frac{\|x\|_2^2}{2}} \cdot \epsilon^{-\frac{\|y\|_2^2}{2}}\\
= &\sum_{j=0}^{\infty}\left\{ \frac{\langle x, y \rangle^j}{\sigma^{2j} \cdot j!} \right\} \cdot\epsilon^{-\frac{\|x\|_2^2}{2}} \cdot \epsilon^{-\frac{\|y\|_2^2}{2}}
\end{aligned}
$$
For further convenience, we refactor the expression (using $c$ for more compact notation):
$$
\begin{aligned}
K(x,y) = &\sum_{j=0}^{\infty}\left\{\frac{\epsilon^{-\frac{\|x\|_2^2}{2}}}{\sigma^j \cdot \sqrt{j!}} \cdot \frac{\epsilon^{-\frac{\|y\|_2^2}{2}}}{\sigma^j \cdot \sqrt{j!}} \cdot \langle x, y \rangle^j \right\}\\
= &\sum_{j=0}^{\infty}\left\{ c_{\sigma, j}(x) \cdot c_{\sigma, j}(y) \cdot \langle x, y \rangle^j \right\}\\
\end{aligned}
$$
And with help of the multinomial theorem, we can express the power of the dot product as follows (using $f$ for more compact notation):
$$
\begin{aligned}
\langle x, y \rangle^j = &\left(\sum_{d=1}^n x_d y_d \right)^j\\
= &\sum_{k_1+k_2+\dots+k_n=j}\left\{ \begin{pmatrix} j\\k_1,k_2, \dots, k_n \end{pmatrix} \prod_{d=1}^n{(x_dy_d)^{k_d}} \right\}\\
= &\sum_{k_1+k_2+\dots+k_n=j}\left\{ \begin{pmatrix} j\\k_1,\dots, k_n \end{pmatrix}^{\frac{1}{2}} \prod_{d=1}^n{x_d^{k_d}} \cdot
\begin{pmatrix} j\\k_1, \dots, k_n \end{pmatrix}^{\frac{1}{2}} \prod_{d=1}^n{y_d^{k_d}} \right\}\\
=: &\sum_{k_1+k_2+\dots+k_n=j}\left\{f_{j,k}(x) \cdot f_{j, k}(y) \right\}\\
\end{aligned}
$$
Now replacing in $K$ will allow us to end the proof:
$$
\begin{aligned}
K(x,y) = &\sum_{j=0}^{\infty}\left\{ c_{\sigma, j}(x) \cdot c_{\sigma, j}(y) \cdot \sum_{k_1+k_2+\dots+k_n=j}\left\{f_{j,k}(x) \cdot f_{j, k}(y) \right\} \right\}\\
= &\sum_{j=0}^{\infty} \sum_{k_1+k_2+\dots+k_n=j}\left\{ c_{\sigma, j}(x) f_{j,k}(x) \cdot c_{\sigma, j}(y) f_{j, k}(y) \right\}\\
= &\langle \phi(x), \phi(y) \rangle\\
&\square
\end{aligned}
$$
Where each $\phi$ is a vector with one entry for every combination of $n$ indices (labeled as $k$) that add up to $j$, and this for each $j$ from 0 to infinity.
hope this helps! Cheers,
Andres